USING MARKETING STRATEGY AS AN EFFORT TO INCREASING VISIT LEVELS IN PENTAGO GARDEN TOURISM DESTINATIONS - Mira Maharani; Ikhtiara Mahreta (JPIM (Jurnal Penelitian Ilmu Manajemen), 2023)
The number of tourism destinations that have sprung up at this time makes competition between tourist destinations in luring tourists, besides that also in increasing tourist visits there needs to be an effort, namely a marketing strategy. Marketing activities play an important role for the survival of a company, so from that in this study will examine increasing the level of visits using marketing strategies. This research is a type of field research with a descriptive approach. The data used are primary data obtained from tourists and secondary data used in the form of existing reference books. Data collection methods are questionnaires, documentation and observation. The results of this study indicate that (1) the marketing strategy used is selecting markets, creating products, distributing, and implementing promotions. (2) The level of tourist visits is quite good and crowded during the holiday season and weekdays (3) the marketing mix that has been carried out has made many visitors come from various regions.